Seismic Performance of FRP-Retrofitted RC Building Using Pushover Analysis - Nabil Mochammad Yusuf; Ari Wibowo; Retno Anggraini (Journal of Novel Engineering Science and Technology, 2026)
The seismic evaluation of existing bank office buildings is critical for ensuring post-earthquake operational continuity. This study investigates a 14-story RC bank building in Kendari using the Nonlinear Static Procedure (NSP) per ASCE 41-17, targeting an Immediate Occupancy (IO) performance level. The initial analysis revealed a critical contradiction: while the structure's global performance appeared to meet the IO target, this assessment was found to be misleading. A detailed, element-based analysis identified a concealed local failure where a critical beam reached the Life Safety (LS) performance level, caused by a non-trivial Positive Moment at the support. A sequential Fiber Reinforced Polymer (FRP) retrofitting strategy was then implemented. The primary contribution of this study is the demonstration of the Failure Migration phenomenon. It was shown that a naive, 'single-point' retrofit (on LS-1) did not solve the problem but merely shifted the failure mode to the next weakest element (LS-2). This sequential retrofitting procedure proved necessary to track the migrating failure, which moved non-linearly between various floors, until all migrating vulnerabilities were eliminated. This finding proves that a sequential procedure is necessary to address Force Redistribution and achieve a true IO performance. The final minor global base shear increase (0.16%) was only a secondary benefit, confirming the objective was local vulnerability elimination, not a significant increase in global stiffness.